2022
DOI: 10.3389/fcvm.2022.934279
|View full text |Cite
|
Sign up to set email alerts
|

Coronary functional assessment in non-obstructive coronary artery disease: Present situation and future direction

Abstract: Non-obstructive coronary artery disease (CAD), which is defined as coronary stenosis <50%, has been increasingly recognized as an emerging entity in clinical practice. Vasomotion abnormality and coronary microvascular dysfunction are two major mechanisms contributing to the occur of angina with non-obstructive CAD. Although routine coronary functional assessment is limited due to several disadvantages, functional evaluation can help to understand the pathophysiological mechanism and/or to exclude specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Patients who experienced this clinical condition are termed INOCA, a syndrome reflecting the well-specified role of CMD which is sustained by a different aetiology with symptoms and signs of myocardial ischaemia [ 37 , 38 , 39 ]. Several recently published studies using multimodal protocols to comprehensively study coronary physiology have revealed that a marked percentage of patients in whom INOCA occurs differ in the underlying form of the coronary microvascular disease [ 23 , 40 , 41 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who experienced this clinical condition are termed INOCA, a syndrome reflecting the well-specified role of CMD which is sustained by a different aetiology with symptoms and signs of myocardial ischaemia [ 37 , 38 , 39 ]. Several recently published studies using multimodal protocols to comprehensively study coronary physiology have revealed that a marked percentage of patients in whom INOCA occurs differ in the underlying form of the coronary microvascular disease [ 23 , 40 , 41 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, CMD is a pathophysiological entity, known as ischaemia and no obstructive CAD (INOCA), in which coexist ischaemia and no obstructive CAD are linked, the disease results in chest pain that develops over time, leading to further progression and is characterized by the presence or absence of coronary macrovascular disorder responsible to evoke an epicardial obstructive CAD [ 37 , 38 , 39 ]. Despite patients with INOCA from CMD experiencing steadily high prevalence and important prognostic course and consideration in both genders, it occurs, especially in women [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to acknowledge the weakness of coronary angiography to assess lumen geometry, plaque components, and presence of thrombus. 6 Indeed, plaque rupture has been identified using intravascular ultrasound in 40% of the MINOCA cases. 7 Our case confirms that OCT can definitely identify the morphologic hallmark of STEMI including plaque rupture and thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inflammatory response is not limited to the ruptured plaque and the adjacent myocardium, but may affect the entire heart, leading to severe consequences, such as cardiomyocyte death. Moreover, spontaneous thrombolysis, a recognized factor in NO-CAD, may be responsible for ischemia/reperfusion injury, resulting in: an increase in ROS, exacerbation of inflammation and even cell death via mechanisms such as necrosis, apoptosis, or ferroptosis [62]. A recent clinical trial confirmed this thesis, wherein the concentration of high sensitivity C-reactive protein (hsCRP), an inflammatory marker, emerged as a stronger predictor of future cardiovascular events and mortality than cholesterol concentration [63].…”
Section: Inflammationmentioning
confidence: 99%